Effects of Solidity Ratio on Performance of OWC Impulse Turbine - Ying Cui (Advances in Mechanical Engineering, 2015)
Oscillating water column (OWC) wave energy converters, which are capable of extracting power from ocean waves, have been constructed and adopted worldwide. An essential component of an OWC system is the impulse turbine, which plays a significant role in converting the energy of bidirectional airflow into mechanical shaft power. To optimize the starting characteristics and conversion efficiencies of impulse turbines, a considerable number of studies have been conducted to improve their geometric construction. This paper verifies a numerical model established in FLUENT 14.5 with preexisting experimental data and subsequently explores the effects of the solidity ratio on turbine performance. The results show that the coherence between computed and measured data is satisfactory. In addition, they reveal that a solidity ratio of 0.63 is suitable and is recommended for future research.